2017
DOI: 10.1530/joe-17-0148
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone increases production of C-type natriuretic peptide in the sheep brain

Abstract: Although C-type natriuretic peptide (CNP) has high abundance in brain tissues and cerebrospinal fluid (CSF), the source and possible factors regulating its secretion within the central nervous system (CNS) are unknown. Here we report the dynamic effects of a single IV bolus of dexamethasone or saline solution on plasma, CSF, CNS and pituitary tissue content of CNP products in adult sheep, along with changes in CNP gene expression in selected tissues. Both CNP and NTproCNP (the amino-terminal product of proCNP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…NPPC expression is upregulated by estrogen 15 , 16 , dexamethasone 17 , gonadotropin-releasing hormone 18 , and transforming growth factor-β (TGF-β) 19 in various cell types. We recently reported that TGF-β in granulosa cells promotes NPPC expression to maintain oocyte meiotic arrest 20 .…”
Section: Introductionmentioning
confidence: 99%
“…NPPC expression is upregulated by estrogen 15 , 16 , dexamethasone 17 , gonadotropin-releasing hormone 18 , and transforming growth factor-β (TGF-β) 19 in various cell types. We recently reported that TGF-β in granulosa cells promotes NPPC expression to maintain oocyte meiotic arrest 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Since its discovery, the initial expression profiling descriptions of CNP in the pituitary have been linked with the control of growth and reproduction [1,[47][48][49], although direct functional effects of CNP on these endocrine axes remain poorly described. Several studies reinforced the position of CNP as the major natriuretic peptide of the anterior pituitary [9][10][11]44].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, somatostatin 1.1 (sst1.1) is uniquely present in the dorsal CSF-cNs of zebrafish, marking this specific subset ( Djenoune et al, 2017b ). Neuropeptide C (Nppc), urocortin 3 (Ucn3), and tachykinin 3 (Tac3) also serve as biomarkers for CSF-cNs in zebrafish ( Wilson et al, 2017 ; Prendergast et al, 2023 ). In contrast, in macaque monkeys, the vasoactive intestinal peptide (VIP) is a distinct marker for CSF-cNs ( LaMotte, 1987 ).…”
Section: The Molecular Markers Of Cerebrospinal Fluid Contacting Neuronsmentioning
confidence: 99%